Potential role of thioredoxin in immune responses in intestinal lamina propria T lymphocytes - Sido, Bernd; Giese, Thomas; Autschbach, Frank; Lasitschka, Felix; Schröder-Braunstein, Jutta; Meuer, Stefan (European journal of immunology, 2005)
Thioredoxin (TRX) is a ubiquitous oxidoreductase with strong co-cytokine, chemoattractant and anti-apoptotic activities. TRX expression was found to be particularly elevated in the intestinal mucosa, where its physiologic function is entirely unknown. Here, we demonstrate a high level of TRX expression in lamina propria T cells (LP-T) as opposed to autologous peripheral blood T lymphocytes (PB-T). Addition of recombinant human TRX (rhTRX) to PB-T enhances TRX gene expression. This autoregulation involves the calcineurin signaling pathway, as rhTRX antagonizes the cyclosporine A (CsA)- and tacrolimus-mediated suppression of TRX gene expression. Similarly, rhTRX reverses the suppression of IL-2 mRNA production by CsA and enhances cytokine production preferentially in prestimulated cells. The differential TRX expression in LP-T versus PB-T may thus contribute to the high-level, CsA-resistant IL-2 production characteristic for CD2-stimulated LP-T. Inversely, inactivation of TRX in LP-T through inhibition of TRX reductase abolishes cytokine gene expression. TRX may play a key role in the specialized intestinal microenvironment in amplifying immediate immune responses of LP-T whenever appropriate costimulation of LP-T is provided.